Students’ Perception of The Use of YouTube as A Digital Platform in Vocabulary Mastery - Masduqi, Harits; Azizah, Fitri Zakiyatul (JLA (Jurnal Lingua Applicata), 2024)
YouTube videos are one of the media that could be used to improve students' vocabulary mastery. This survey study investigated how students felt about using YouTube as a digital platform for vocabulary mastery. It involved 36 students of the Department of English, Faculty of Letters, Universitas Negeri Malang. The researcher collected data by distributing questionnaires online to the English Language Education (ELE) students of the 2021 cohort. The questionnaires’ items were adapted from several questionnaires developed by Slavin (1995) and Nelson-Smith (2008). The findings indicated that students had a positive perception of using YouTube and enjoyed it because YouTube videos are a helpful tool to improve student's vocabulary and can be used as an alternate form of media for independent learning. Additionally, students found that watching YouTube helped them increase the number of new vocabulary words they learned, improved their learning motivation, and encouraged critical and creative thinking.